Karakteristik Pribadi Konselor Berkualitas Dalam Kisah Kiai As’ad Syamsul Arifin - M.Syakur; Hafifuddin Nur (Fakultas Dakwah Universitas Ibrahimy, 2022)
The counselor is a figure who is always required to continue to develop his personal qualities, the counselor’s personal qualities should be in accordance with their own culture. This study aims to examine the content of personality values in the story of Kiai As’ad Syamsul Arifin which was later adopted as the concept of the counselor’s personal quality according to the culture of the Salafiyah Syafi’iyah Islamic boarding school Sukorejo Situbondo. The research method used is a qualitative approach of the type of Gadamerian Hermeneutics which aims to interpret and understand the text in the story of Kiai As’ad Syamsul Arifin to achieve a complete meaning. The results of the study found seven personality values that can be developed into personal characteristics of qualified counselors, including: religious, nationalist, honest, patient, socially caring, communicative, and responsible.